Blood lactate removal after a rowing all-out test depends on the active protocol proposed - Cristi-Montero, C.; Rodriguez-Rodriguez, F.; Mendoza-Muñoz, J.; Baronti-Correa, F.; Leiva-Olivares, S.; Rojas-Hube, M.; Bresciani, G. (Science & Sports, 2015)
Aims: In sports competition recovery is considered fundamental, especially in those modalities that require competing repeatedly within one contest. One of the main concerns regarding the short recovery period during repeated-based competitions is the accumulation of blood lactate, which may impair muscle function on a metabolic basis. Therefore, the aim of this study was to compare the lactate concentration ([Lac]) removal rate with different recovery active protocols after an all-out rowing test. Materials and methods: The participants were chosen at random from the Naval School and subjected to four removal protocols (rowing, cycling, running and complete rest). Blood lactate samples were taken at rest and subsequent to the all-out test (0, 5, 10, 15, 20, 25 and 30 min). Results and conclusion: At minute 20, the running protocol presented similar blood [Lac] values as resting sample, whereas rowing reached it on 25, and cycling on 30 min. Additionally, a passive 30 min rest after the last blood sampling indicated that all protocols were able to reduce the blood [Lac] to rest values, including the resting group. In this sense, this study indicates that different active protocols induce a faster blood [Lac] removal after high-intensity rowing. Finally, treadmill running may be a feasible tool to boost blood [Lac] removal after rowing trials within the same competition.